Career Maturity Growth Curve and Sex-Role Stereotypes of Korean Adolescents. (June 2013) - Yon, Kyu Jin; Choi, Wonseok; Goh, Michael
This longitudinal study investigated the career maturity growth curve of Korean Adolescents from 4th grade to 12th grade. The participants consisted of 3, 241 male and 3, 029 female students from the Korea Youth Panel Survey, a nationwide longitudinal study of South Korean adolescents. The present study explored the shape of the career maturity growth curve and the effects of sex-role stereotyping, gender, and socioeconomic status on the career maturity growth curve. Results indicated that the career maturity of Korean adolescents from 4th grade to 12th grade develops in a cubic manner. The authors found significant effects of household income and mother's education level on the trajectory of the career maturity growth curve. The authors also found a significant, negative longitudinal relationship between sex-role stereotyping and career maturity as well as an interaction effect between gender and sex-role stereotyping on career maturity change. Implications for career guidance for Korean adolescents are discussed.